Perception of preventing behavior against COVID-19 among Indonesian industrial workers - Iwan Muhamad Ramdan; Krishna Purnawan Candra; Muhammad Sultan (International Journal of Public Health Science (IJPHS), 2022)
The coronavirus disease 2019 (COVID-19) pandemic is continuing, but companies have been allowed to continue their business with the obligation strictly to apply health protocol. A cross-sectional study aimed to examine the perception of COVID-19 and its prevention behavior based on the health belief model was conducted on 285 industrial workers from eight company types sampled by online survey. The results show that most workers have poor COVID-19 perceptions (54.7%). However, the workers showing good behavior (61.1%) in preventing COVID-19 transmission. Gender (p=0.009), education background (p=0.017) and company types (p=0.001) were related to the COVID-19 perception. In addition, the perceptions related to the behavior in preventing COVID-19 transmission (p=0.000). Except cues to action, all perception components, i.e., perceived susceptibility (p=0.000), seriousness (p=0.005), benefits (p=0.000), barriers (p=0.000), and self-efficacy (p=0.000) related to behavior to prevent COVID-19 transmission. However, the perception components show a weak correlation with preventing behavior (r=0.167-0.234). The information types were related to perceived barriers (p=0.046) and cues to action (p=0.007). Maintain a safe distance (p=0.029), using a face mask (p=0.039), and eat nutritious food (p=0.019) related to information types. The increase of COVID-19 perception is the key to improve industrial workers' behavior to prevent the COVID-19 transmission.